An exploratory study of perfectionism, professional factors and psychological well‐being of dentistry academics. (1st February 2021) - Teixeira, H; Lalloo, R; Evans, JL; Fuss, J; Pachana, NA; Nović, A; Burton, NW
Abstract: Background: Well‐being might be lower among dentistry professionals than other health professionals, and differ by personal, professional and sociodemographic factors. Few studies have considered dentistry academics who have different work roles and functions than clinicians. This exploratory study focused on well‐being among dentistry academics and aimed to explore associations with perfectionism, professional factors and sociodemographics. Method: An online survey was carried out with academic staff in Dentistry and Oral Health departments of nine Universities in Australia and New Zealand. Well‐being was assessed using the 22‐item Psychological General Well‐Being Index, with a maximum score of 110 indicating good well‐being. Perfectionism was assessed using the 8‐item Short Almost Perfect Scale, with a maximum score of 56 and a higher score indicating perfectionism. Twenty items were used to assess professional and 7 items assessed sociodemographic factors. Associations were explored using correlation and multiple linear regression. Results: There was no significant bivariate association between perfectionism and well‐being. Multiple linear regression indicated a significant association between hours of undergraduate teaching and psychological well‐being, after adjustment for age, gender, income and overall health. Conclusion: This exploratory study showed poor well‐being among dentistry academics, particularly in those teaching undergraduate students for more than 6 h/week.